The positivist demand and the betrayed tradition of tacit knowledge in an African thought system : fractures in Esan epistemology - Ukpokolo, Isaac Ehaleoye (Array, 2019)
The present paper identifies a certain crisis in the African condition represented in the betrayal of the tradition of tacit knowledge in Esan thought system, leaving behind fractures in the people’s epistemology. Behind this situation is the positivist demand for verification and confirmation in the pursuit of a reliable epistemology. In navigating the condition of contemporary Esan thought system, the paper reveals that the tradition of tacit knowledge has been underplayed and rejected by the demands of modernity. Since the epistemology of a people influences the way they engage their reality, confront their problems and encounter their difficulties, and since the African condition rests on fractured epistemologies (as exemplified in Esan epistemic stances), the paper presents a picture of a tradition that is ruptured and in need of healing and the retrieval of its soul. This tradition is encapsulated in tacit knowledge and implicit ideals. It is only in the execution of the retrieval that we will be able to bring to the fore a reliable epistemological program that will treat the Esan condition, writ large, Africa and reveal the essence of the common good. The paper presents some instantiations of the betrayed tradition as expressed and employed in aspects of the people’s lives such as health care and social relations. By this, the connection among epistemology, ontology, social order and morality becomes explicit.